If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -7(x + 3) = -36 Reorder the terms: 4x + -7(3 + x) = -36 4x + (3 * -7 + x * -7) = -36 4x + (-21 + -7x) = -36 Reorder the terms: -21 + 4x + -7x = -36 Combine like terms: 4x + -7x = -3x -21 + -3x = -36 Solving -21 + -3x = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + -3x = -36 + 21 Combine like terms: -21 + 21 = 0 0 + -3x = -36 + 21 -3x = -36 + 21 Combine like terms: -36 + 21 = -15 -3x = -15 Divide each side by '-3'. x = 5 Simplifying x = 5
| 2.53-x=6.8 | | a-3=2.45 | | 16p/7=(2p-7)/4 | | y-4=-2/3 | | -12/x=3/4 | | 2x+33=3+7x-5 | | 9x-4=2x+12 | | 6y*y/6y | | B^2+4b=8 | | 6t^2+24t-100=0 | | 3x^3+4x^2+8x+6= | | 6x+6y=31.78 | | X^2+2x-99999=0 | | 6x+6y=31.95 | | X/5=36/4 | | x=sqrt(9x+63-3) | | 6n+10=19 | | 20x+25y=11700 | | 9(2-3x)-29=8x-(x-23) | | x=0.34x | | 5n+3=21 | | 3/7/8-1/5/8 | | P-11=39 | | 6.2=2.2+r | | 4-4x=5+6x | | 42-r=2 | | (2x)/(9-x^2)0 | | -0.5x+2.26=1.345 | | T+28=51 | | (x-2)(x+2)=32 | | .50/8x | | m-9=-13 |